Subatmospheric boiling study of the operation of a horizontal thermosyphon reboiler loop: Instability - Agunlejika, Ezekiel O.; Langston, Paul A.; Azzopardi, Barry J.; Hewakandamby, Buddhika N. (Elsevier, 2016)
Distillation and chemical processing under vacuum is of immense interest to petroleum and chemical industries due to lower energy costs and improved safety. To tap into these benefits, energy efficient reboilers with lower maintenance costs are required. Here, a horizontal thermosyphon reboiler is investigated at subatmospheric pressures and low heat fluxes. This paper presents detailed experimental data obtained using Wire Mesh Sensor in a gas-liquid flow with heat transfer as well as temperatures, pressures and recirculation rates around the loop. Flow regimes which have been previously identified in other systems were detected. The nature of the instability which underpins the mechanisms involved and conditions aiding instability are reported. Churn flow pattern is persistently detected during instability. The nature of the instability and existence of oscillatory churn flow are interconnected